The field investigation of erosion and debris flow processes in catchment basin of the duruji river - Gavardashvili, Givi; Ayyub, Bilal M. (Italian journal of engineering geology and environment, 2011)
For the effective protection of the population of the town of Kvareli in Georgia from debris flow formed on the Duruji River, the critical places on the river-bed of Duruji, where over flow of debris flow is possible, were identified. Erosion coefficients of mountain slopes with debris flowing into the basin of Duruji River, which establishes links between the class of erosion and degree of damage of a slope, were explored. Maximum charges on debris flow of river Duruji in different provisions were established, through which, at a following stage of an ongoing project, anti-debris flow structures are planned and designed. Using the theories of reliability and risk, probability distributions of the maximum charges of debris flow formed on river Duruji were examined including the suitability of using the Weibull probability distribution. The reliability of new springboard type debris flow protection structures and associated risk profiles in the case of joint and separate dynamic and statistic influences of debris flow on the structures were assessed. Results from this investigation enabled us to predict effectively erosive-debris flow processes in the riverbed of Duruji, and introduce new ecological measures engineered to ensure the effective protection of the population of the town of Kvareli in Georgia and contiguous territory of the Duruji River from debris flow.